Reliability of transcutaneous bilirubin estimation during phototherapy in term infants: A hospital-based observational study - Jehangir Allam Bhat; Sajad Ahmad Sheikh; Zubair Ahmad Wani; Roshan Ara; Sami Ullah Bhat (Sahel Medical Journal, 2020)
Background:Blood sampling method is the most common but invasive method for bilirubin estimation. Transcutaneous bilirubin (TCB) estimation, on the other hand is non-invasive. Objectives: The aim was to compare neonatal bilirubin estimation by serum bilirubin and transcutaneous bilirubinometer methods both pre- and during phototherapy and establish the precision of transcutaneous bilirubinometer. Materials and Methods: This prospective hospital-based observational study was conducted on 350 term neonates over a period of 2 years. Bilirubin was estimated in all newborn by both serum bilirubin and transcutaneous method, at the time of admission in nursery (prephototherapy), at 6 h after phototherapy (while neonates were still under phototherapy treatment), and at withholding phototherapy, and a photo opaque patch of 2.5 cm was used to cover the area on midforehead and transcutaneous bilirubin was estimated from this area after removing it during phototherapy. All data were tabulated and analyzed by relevant statistical tests. Results: A total of 350 term healthy newborns with mean gestational age of 38 ± 2 weeks and mean birth weight of 2.97 ± 0.9 kg were studied. Correlation analysis revealed a significant correlation between total serum bilirubin and transcutaneous method (TCB) measurements of bilirubin. When these methods were compared at pre-phototherapy, at 6 hours after phototherapy and before withholding phototherapy, correlation coefficient(r) of 0.9571, 0.7988, and 0.9206 were seen respectively. The precision levels of transcutaneous bilirubinometer (BiliCheck™) were good because plotting of Bland–Altman graphs showed maximum (>97%) data within agreement limits at all stages of phototherapy. Conclusion: Our study revealed good correlation and precision of transcutaneous bilirubinometer both before and during phototherapy. Thus, it supports the previous studies which justify the use of transcutaneous bilirubinometer in assessing newborn jaundice during phototherapy.